Uji Antiinflamasi Infusa Bunga Seroja (Nelumbo nucifera Gaertn) Pada Struktur Mikroanatomi Ginjal Mencit (Mus musculus) yang Mengalami Stres - Rahmawati, Yuniarti, Diah Wulandari Rousdy (Universitas Tanjungpura, 2015)
Lotus (Nelumbo nucifera Gaertn) is an aquatic plant that contains various kinds of phytocemical compounds, one of which is quercetin that has the potentiality to suppress inflammation. The arm of this research was to observe the anti-inflamation effect of Lotus infused water on kidneys mikroanatomical structure of mice (Mus musculus). The test subjects used in this research were 2 months old male swiss strain mice. This research utilized the completely randomized design (CRD) with 5 treatments and 3 replication each. The treatments groups were the given Lotus infused water orally consist of 5,6 mg/g BW, 8,4 mg/g BW and 11,2 mg/g BW dosages for 7 days, the normal control groups and the negatif control groups. Kidney microanatomical preparations were made using paraffin method with HE coloring. The result of this research show this research shows that stressing the mice may affect their kidneys microanatomical structure in forms of cell swelling (edema), hidropic degenerations, necrosis, and atrophy. The consumtions of Lotus infused water can suppress the inflammation on kidneys mikroanatomical structure of mice. The changes on kidneys tubulus and glomerolus of mice may start to be visible on the consumtion of 5,6 mg/g BW dosage of infused water.